A global comparison of suicide and non-suicide terrorism. Issue 2 (4th May 2021) - Guler, Ahmet; Demir, Mustafa
ABSTRACT: Suicide terrorism has become an increasingly popular attack strategy among terrorist organisations over the last 40 years. The number of empirical studies on suicide terrorism has increased, but further research is necessary to understand the strategies of terrorist organisations that engage in suicide terrorism. Using the Situational Crime Prevention (SCP) theory as the framework, this study examines whether suicide terrorism differs by region, attack type, target type, weapon type, and type of terrorist organisation from non-suicide terrorism in global terrorist attacks that occurred between 1981 and 2017. Bivariate and multivariate analyses show that relative to non-suicide terrorism, suicide terrorism is more likely to occur in the Middle East and Africa, involve bombing/explosion as attack type, explosives/incendiary devices as weaponry, target security forces, and be committed by religious-based terrorist organisations. The results of this research indicate that situational terrorism prevention approach needs to be revised to consider the role of ideology in terrorist attack strategy since the ideology of a terrorist organisation plays a significant role in suicide terrorism. The findings of the research and its policy implications are discussed, and further research is warranted to expand the base of knowledge about suicide terrorism.